ANALYSIS OF THE LEADING ECONOMICS SECTOR OF BANTEN PROVINCE BEFORE AND DURING THE COVID-19 PANDEMIC - Dewi, Mia Clarissa; Wawanudin, Wawanudin; Kurniawan, Bambang (Yudishtira Journal : Indonesian Journal of Finance and Strategy Inside, 2025)
The Covid-19 pandemic that occurred throughout 2020 caused the economic condition of the Banten Province to contract or grow negatively by 3.38%. Of all the existing sectors, some of them were able to grow positively. With all the potential possessed by Banten Province, it is necessary to conduct a study of the leading sectors needed for planning for sustainable development. The purpose of this research is to analyze the leading sectors before the pandemic and after the Covid-19 pandemic. The approach used in this research is quantitative with the method of location quotient (LQ) analysis, shift share and typology klassen. Based on the results of the analysis, there are three leading and competitive sectors to be developed which are categorized as advanced and rapidly growing sectors prior to the Covid-19 pandemic, namely: a) wholesale and retail trade; repair of cars and motorcycles; b) transportation and warehousing; c) and real estate. Meanwhile, during the Covid-19 pandemic, the water supply, waste management, waste and recycling sectors became a sector that still survived as a superior, competitive sector and was categorized as a developed and rapidly growing sector.